Public service in radio program content analysis of Barangay 1296 of DXAB 1296 ABS-CBN Davao City - Gayorgor, Hanna Mae B.
This study is a content analysis of the radio program Barangay 1296 of DXAB 1296, ABS-CBN Davao City. It aims to identify the pressing issues and concerns in society nowadays, as well as the advetisements aired, including public service announcements. This also provides an analysis on how the anchor, reporter, and concerned person presented, treated, and delivered the topic or issue. The data was gathered through recording of the program from January 21 to February 1, 2008, Mondays to fridays from 9:00 to 11:00 AM, for a total of ten airing days. After the recording, the data was transcribed and analyzed through tabulating and obtaining the frequency of each variables and elements. After obtaining the frequency, the results were analyzed by looking at each element under each variable being presented. After analyzing the pieces of data, it was found out that the radio programs's content were primarily news, issues, and concerns in Davao City and Region XI as a whole. The highlight of the program which makes it a public service-oriented program was the so called panawagan that provides an opportunity to the indigents to seek solutions to their problems. This panawagan has the actual participation of the concerned person airing his/her problem. The focus of the panawagan concerns health and financial matters. Moreover, news was focused on social issues, specifically on barangay and government matters. The recommendation would be that further studies regarding the existence of the panawagan in other radio stations should be conducted in order to know if it is indeed a unique content of radio programming, and if it also answers the social needs of its community
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts